Tinjauan Yuridis Putusan Hakim Terhadap Perkara Tindak Pidana Perdagangan Orang (Putusan No.523/Pid.Sus/2022/Pn.Mks) - Amiruddin Lanurung; Ambo Esa; Ilan, Riswedi (Pledoi Law Jurnal, 2024)
ABSTRACT: So this research was conducted with the aim of knowing the application of material criminal law and the judge's consideration in imposing criminal sanctions for traffickers in verdict number: 523/Pid.Sus/2022/PN.Mks. This research is categorized as empirical normative legal research with the problem approach used is empirical juridical. Data obtained by means of interviews and documentation, sourced from primary, secondary and tertiary legal materials. Data analysis is done by inductive and deductive methods. The results showed that the application of material criminal law in accordance with Article 12 of the Trafficking in Persons Act with a minimum sentence of 3 years and a maximum sentence of 15 years imprisonment in Decision Number: 523/Pid.Sus/2022/PN.Mks was appropriate. The judge's consideration in imposing criminal sanctions is to look at the criminal offence, the provisions of criminal sanctions applied in the law, the prosecutor's indictment, the defendant's testimony, witness testimony, evidence and articles in the criminal law regulations and the facts revealed in the trial.   ABSTRAK: Sehingga penelitian ini dilakukan dengan tujuan untuk mengetahui penerapan hukum pidana materil dan pertimbangan hakim dalam menjatuhkan sanksi pidana bagi pelaku perdagangan orang pada putusan nomor: 523/Pid.Sus/2022/PN.Mks. Penelitian ini kategori penelitian hukum normatif empiris dengan pendekatan masalah yang dipakai ialah yuridis empiris. Data diperoleh dengan cara wawancara dan dokumentasi, bersumber dari bahan bahan hukum primer, sekunder maupun tersier. Analisis data yang dilakukan adalah dengan metode induktif dan deduktif. Hasil penelitian menunjukan bahwa penerapan hukum pidana materil sesuai pasal 12 Undang-Undang Tindak Pidana Perdagangan Orang dengan ancaman hukuman minimal 3 tahun dan maksimal 15 tahun penjara pada putusan Nomor : 523/Pid.Sus/2022/PN.Mks telah sesuai. Pertimbangan hakim dalam menjatuhkan sanksi pidananya ialah melihat pelanggaran pidananya, ketentuan sanksi pidana diterapkan dalam undang-undang, dakwaan jaksa penuntut  umum, keterangan terdakwa, keterangan saksi, barang-barang bukti dan pasal-pasal dalam peraturan hukum pidana dan fakta-fakta yang terungkap dalam persidangan.